ASSET DESIGN FOR AN EDUCATIONAL GAME PROTOTYPE "BIMON: BIJAK DALAM BERMEDIA ONLINE" FOR CHILDREN AGED 10–15 YEARS - Salsabila, Kharisma Mutiara (Journal of Design and Creative Media Studies, 2026)
This research designs visual assets for the "BIMON: Bijak dalam Bermedia Online" educational game prototype as a digital literacy medium for children aged 10–15. The background highlights that high intensity of smartphone and social media use among children is not matched by adequate understanding of digital risks such as short attention span, scrolling addiction, cyberbullying, and phishing. Text-based educational media is considered less effective for digital native generations, so more engaging and relevant media is needed. The Double Diamond method (Discover, Define, Develop, Deliver) was employed. Data were collected through interviews with child psychologists, surveys of children aged 10–15 in Lidah Wetan, Surabaya, and literature studies, then analyzed using the Miles and Huberman model. The design outputs include slice-of-life visual assets comprising characters, backgrounds, objects, and user interface (UI) elements, along with four simulation mini-games addressing the four digital issues. Validation results showed an 86.54% feasibility score from media experts and 93.75% from trials with 10 target users, both in the "very good" category. Therefore, the "BIMON" prototype assets are declared highly feasible for use as a digital literacy learning medium for children aged 10–15. Keywords: game assets, educational game, digital literacy, children aged 10–15 years, character design, visual communication design, double diamond.